Modern Monetary Theory In An Islamic Monetaryperspective - Munthe, Salpiani; Imsar, Imsar (GEMA EKONOMI, 2023)
Modern Monetary Theory or MMT is currently considered capable of making a country no longer dependent on the value of taxes and debt. Printing as much money as needed in the realsector will not make printing money cause inflation as it has been. There have not been many studies that discuss this MMT from an Islamic economic point of view. This study aims to provide new insights for monetary policy, especially Islamic monetary, in developing monetary policy in accordance with the development of exchange instruments or money circulation which is currently very rapid. This research is a qualitative research with a library research approach. The data sources used are primary data sources (Ibn Khaldun's book and Umer Chapra's book), secondary data (supporting books, journals, and other literature). The data analysis used is descriptive analysis and content analysis (conten analysis). Data assurance through triangulation, namely sources, methods, investigators and theories. The result of this researchis that modern monetary theory (MMT) can be one of the options in overcoming an economicrecession, in line with the Islamic economy which emphasizes more on real investment than investment on paper, with strict requirements. Modern Monetary Theory (MMT) can be adopted to help increase people's purchasing power so that it has an impact on increasing state incomewithout having to increase foreign debt.